STATUS OF HUMUS IN THE SOILS OF CHIRCHIK RIVER TERRACES - Rushana Kholmurodova; Tohirov Alpomish (International Engineering Journal For Research & Development, 2020)
The article describes the humus of the irrigated soils of the right and left sides of the Chirchik River cone, the upper (Upper Chirchik, Kibray), middle (Middle) and lower (Chinoz and Kuyichirchik) parts (on the terraces).